Comparison of the efficacy of fish oil and probiotic supplementation on glucose and lipid metabolism in patients with type 2 diabetes: a systematic review and network meta-analysis - Mei Zhang; Fan Yang; Qiu Feng; Yanghong Ou; Jiaxing Zhang; Haiyan Wan; Hongyi Cao; Peng Ning (Diabetology & Metabolic Syndrome, 2024)
Abstract Background Abnormalities in glucose and lipid metabolism contribute to the progression and exacerbation of type 2 diabetes mellitus (T2DM). Fish oil and probiotics are dietary supplements that have the potential to improve glucose and lipid metabolism. However, their efficacy remains unclear in T2DM patients. Methods PubMed, Embase, and the Cochrane Library were retrieved to collect randomized controlled trials (RCTs) on the efficacy of fish oil or probiotic supplementation in T2DM patients from the database inception to December 13, 2023. Primary outcome indicators encompassed glycated hemoglobin (HbA1c), homeostatic model assessment for insulin resistance (HOMA-IR) and blood lipid profile (triglyceride (TG) and total cholesterol (TC). Secondary outcome indicators included inflammatory markers such as tumor necrosis factor -α (TNF-α) and adipocytokine (including leptin and adiponectin). The R software was used for statistical analysis, and GraphPad Prism was used for figure rendering. Results A total of 60 RCTs involving 3845 T2DM patients were included in the analysis. The results showed that the probiotics (Bifidobacterium, Lactobacillus, Lactococcus, Propionibacterium, etc.) were more effective in reducing HOMA-IR than fish oil (Surca = 0.935). Bifidobacterium demonstrated the highest efficacy in reducing HbA1c levels (Surca = 0.963). Regarding lipid metabolism, fish oil was superior to probiotics in lowering TG and TC levels (Surca values of 0.978 and 0.902, respectively). Furthermore, fish oil outperformed probiotics in reducing TNF-α (Surca = 0.839) and leptin (Surca = 0.712), and increasing adiponectin levels (Surca = 0.742). Node-splitting analysis showed good consistency (P > 0.05 for direct, indirect, and network comparison across various interventions). Conclusions In T2DM patients, fish oil was more effective than probiotics in regulating lipid metabolism. Probiotics outperformed fish oil in regulating glucose metabolism particularly; specifically, Bifidobacterium showed higher efficacy in reducing blood glucose.